Soliton solutions for the super mKdV and sinh-Gordon hierarchy - Gomes, J. F.; Ymai, L. H.; Zimerman, A. H. (Elsevier B.V., 2006)
The dressing and vertex operator formalism is emploied to study the soliton solutions of the N = I super mKdV and sinh-Gordon models. Explicit two and four vertex solutions are constructed. The relation between the soliton solutions of both models is verified. (c) 2006 Elsevier B.V. All rights reserved.